Mermaid syndrome in Enugu, Nigeria - Johnpaul Ejikeme Nnagbo; Chukwudi Cyril Dim; Hyginus Uzo Ezegwui (Nigerian Journal of Medicine, 2020)
Mermaid syndrome is a type of gross fetal anomaly, characterized by the fusion of lower extremities, absent external genitalia, and apparently well-formed abdomen, chest, upper extremities, and head. The neonatal mortality rate due to this anomaly is high, but the disorder is relatively rare. Hence, few cases have been reported in the medical literature, and none in University of Nigeria Teaching Hospital, Ituku-Ozalla, Enugu State.